The effect of immunosuppressive agents on immunogenicity of pneumococcal vaccination: A systematic review and meta-analysis - van Aalst, Mariëlle; Langedijk, Annefleur C.; Spijker, René; de Bree, Godelieve J.; Grobusch, Martin P.; Goorhuis, Abraham (Vaccine, 2018)
•Immunosuppressive agents mitigate the immune response to pneumococcal vaccination.•Anti-TNFα is associated with a better response than DMARDS or combination therapy.•Short-term response to PCV is lower than to PPSV when using immunosuppressive drugs.•Uniform definitions of seroconversion and correlates of protection are needed. Patients with a weakened immune system due to immunosuppressive treatment are at increased risk of infection with Streptococcus pneumoniae. Although pneumococcal vaccination is highly recommended for those patients, the effectiveness of pneumococcal vaccination in this population remains largely unknown. Therefore, the objective of this PROSPERO-registered systematic review and meta-analysis was to evaluate the effect of the most commonly prescribed immunosuppressive agents such as azathioprine, methotrexate, anti-Tumor Necrosis Factor α (TNFα), or rituximab, on the initial serologic response to pneumococcal vaccination in patients with auto-immune disease. We included 22 articles comprising 2077 patients, of whom 1623 were treated with immunosuppressive agents, and 454 were controls. The findings of our systematic review indicate that, in patients treated with immunosuppressive medication and compared to controls, the initial serologic response to pneumococcal conjugate vaccine (PCV) and pneumococcal polysaccharide vaccine (PPSV) are impaired. Moreover, this impaired response was more profound after PCV than after PPSV. We hypothesize that the immunosuppressive medication mainly compromises the cellular immunity, explaining the more severely reduced response rate to PCV (which induces a T-cell dependent immune response), compared to PPSV. Treatment with TNFα blocking agents was associated with a more favorable response, compared to patients treated with other immunosuppressive medication. Targeted research applying uniform correlates of protection is needed to bridge the knowledge gap in vaccination immunology in this patient group. PROSPERO registration: CRD42017058364.